Geographical variation in clinical signs and prevalence of Leishmania sp. infection among dogs in Fortaleza, Ceará State, Brazil - Freitas, José Claudio Carneiro de; Nunes-Pinheiro, Diana Célia Sousa; Abreu, Cyntia Rafaelle Amaral de (Acta Scientiae Veterinariae, 2018)
Background : : : : Leishmaniosis are anthropozoonosis caused by protozoa of the genus Leishmania, representing a complex of diseases with significant diversity epidemiological and clinical spectrum and can affect 40% of the canine population. Infected dogs may be asymptomatic or may develop canine leishmaniasis (CL), a severe and progressive disease associated with the appearance of clinical signs. Serological tests are frequently used for screening of dogs, however, these techniques present limitations in terms of reproducibility and specificity. In this way, information on the geographical distribution and prevalence of CL is essential to the implementation of appropriate control measures. Therefore, the aim of this study was to determine geographical variations in clinical signs and prevalence of Leishmania sp infections from dogs in Fortaleza, Ceara state, Brazil. Material, Methods & Results: Bone marrow samples of 2829 domestic dogs were collected by puncture for parasitological diagnosis of canine leishmaniasis (CL), being considered positive by the presence of Leishmania sp. All dogs were examined and clinical signs were classified as score 0: no clinical signs, score 1: skin lesions, score 2: visceral signs and score 3: skin lesions + visceral signs. Kruskal-Wallis (p <0.05) was used to compare the scores and parasitological diagnosis among the seven regions of Fortaleza. 72% of dogs were positive, and the regions I and V with the highest prevalence (78.3% and 80%, respectively), however, no significant differences among the seven regions. 55% of infected dogs were asymptomatic and the symptomatic group (45%), 43% of the dogs had skin lesions. 70% of all dogs had ectoparasites. Discussion: These results show that, despite of the campaign against the disease, there is no great progress in the control of visceral leishmaniasis in the urban areas like Fortaleza, which present an easy access in the fight against the disease. The diagnostic in dogs based in the Indirect Fluorescent Antibody Test (IFAT) associated to others factors, like irregular serological inquiry and no-treated performer personal, perhaps made possible the permanence of susceptibility animals in this area, beyond of the high number of asymptomatic and no-identified dogs. In this study, it was observed that 55% of dogs were asymptomatic, without showing evidence of risk of transmission to human population, escaping from controlling methods. From this we can imply that most of these dogs to LC are asymptomatic and the prevalence did not differ significantly in different regions of Fortaleza, requiring equal attention throughout the city. Moreover, our results demonstrate that Fortaleza city has favorable areas for the maintenance of the parasite cycle, with a high risk of transmission to human and canine population, and it requires special attention because of the large number of asymptomatic cases. Therefore, it is necessary to control the population of asymptomatic dogs with more efficient controlling methods, with the change of methodology of serological screening raising the number of detected dogs, reducing the diagnostic time and the use of diagnostic techniques with levels of specificity higher.